Administrative Efforts as a Prerequisite for a Lawsuit at the State Administrative Court - Siti Ruaida Turam; Ahmad Ahmad; Abdullah Yuwafie Maimun; Muhammad Rifa Ali Akbar (Indonesian Journal of Law and Policy Studies, 2024)
Administrative remedies are a dispute resolution mechanism within the realm of administrative law that must be taken before filing a lawsuit with the State Administrative Court . This obligation is affirmed in Law Number 30 of 2014 concerning State Administration and reinforced by Supreme Court Regulation Number 6 of 2018. Conceptually, administrative remedies are intended as an efficient, fast, and proportional internal corrective tool, while also reducing the caseload in court. However, in practice, the effectiveness of this mechanism still raises various problems, both in terms of public understanding and the readiness of government institutions. This research is a normative legal research with a statutory, conceptual, and case approach, using the Jakarta State Administrative Court Decision Number 157/G/2019/PTUN.JKT as the main analytical material. The results of the discussion indicate that although administrative remedies have a strong normative basis, their effectiveness is highly dependent on consistent and responsive implementation by state administrative bodies or officials.